The Assumptive Messianism of the Son of Man. Reflection in the Light of Contemporary Christology - Luciani, Rafael (Editorial Pontificia Universidad Javeriana, 2018)
In the light of the expectations existing in the first century, we present the most relevant features to understand the style of an assumptive messianism, inspired by the figure of the Son of Man, which allows us to interpret the life of Jesus as a solidary surrender. Thus, we review the logic of the imperial power during the intertestamental period, as opposed to the humanizing praxis of the Messiah-Son. The messianic style of Jesus reveals the prophetic and incarnational spirit of Christianity in rescuing the messianic goods that point to a dignified life, especially for the poor, whose utopias deserve to be heard.